1989
DOI: 10.1269/jrr.30.352
|View full text |Cite
|
Sign up to set email alerts
|

9;22 Translocation and bcr rearrangements in chronic myelocytic leukemia patients among atomic bomb survivors.

Abstract: To elucidate the mechanism of leukemia induced by radiation, we studied both chromosome abnormalities and bcr rearrangements of seven CML patients with a history of atomic bomb exposure and 14 CML patients without the exposure. All patients, irrespective of radiation exposure, had 9;22 translocation and rearrangement of the bcr gene in the leukemic cells. Further analysis of breakpoints within the bcr gene demonstrated no distinct difference between the exposed and the non-exposed groups. The present study sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A more relevant issue in this case is whether the CML was induced by the conditioning regimen used for auto‐transplantation. Based on studies of the survivors of the atomic bombs dropped on Hiroshima and Nagasaki in World War II [9], it has long been known DNA‐damaging agents such as ionizing radiation increase the incidence of CML, and in vitro work has shown that the appearance of BCR‐ABL fusion genes can be induced in cells by ionizing radiation [10]. It thus seemed possible that conditioning with cyclophosphamide might have caused DNA breaks that led to the appearance of the BCR‐ABL ‐positive clone in our patient.…”
Section: Commentarymentioning
confidence: 99%
“…A more relevant issue in this case is whether the CML was induced by the conditioning regimen used for auto‐transplantation. Based on studies of the survivors of the atomic bombs dropped on Hiroshima and Nagasaki in World War II [9], it has long been known DNA‐damaging agents such as ionizing radiation increase the incidence of CML, and in vitro work has shown that the appearance of BCR‐ABL fusion genes can be induced in cells by ionizing radiation [10]. It thus seemed possible that conditioning with cyclophosphamide might have caused DNA breaks that led to the appearance of the BCR‐ABL ‐positive clone in our patient.…”
Section: Commentarymentioning
confidence: 99%
“…Tanaka et al [ 92 ] studied chromosomal abnormalities and bcr -locus rearrangements in seven CML atomic bomb survivors and compared with fourteen CML unirradiated patients. They found that all CML patients contained BCR-ABL1 p210 fusion protein.…”
Section: Pfgs Induced By Irmentioning
confidence: 99%
“…One of the intriguing questions is, what predisposes to the translocation in the first place? Although ionising radiation has been implicated (Tanaka et al , 1989) it is more likely a result of the error‐prone non‐homologous end‐joining mechanism (Wiemels & Greaves, 1999; Elliott & Jasin, 2002). The BCR and ABL genes are in close physical proximity in the nucleus (Neves et al , 1999) and it is possible that breaks in the DNA are illegitimately repaired and result in a translocation that gives the cell a survival advantage.…”
Section: The Biology Of Ph+ Allmentioning
confidence: 99%